Assessing recent environmental sustainability in the Spanish network of National Parks and their statutory peripheral areas. (December 2017) - Rodríguez-Rodríguez, David; Martínez-Vega, Javier
Abstract: Land use-land cover (LULC) changes and wildfires in the Spanish Network of terrestrial National Parks (NPs) and their legally designated peripheral areas, including Peripheral Protection Zones (PPZs) and Socioeconomic Influence Zones (SIZs), were assessed as indicators of recent territorial environmental sustainability trends. Level three, Corine Land Cover (CLC) data between 2005 and 2011 were compared. Official wildfire digital data were obtained from the European Commission for the 2005–2011 period. Results show increasing numbers of LULC changes along the protection gradient: NPs < PPZs < SIZs. NPs were, in general, highly stable regarding LULC changes and less affected by wildfires, which suggests high environmental effectiveness of legal and managerial protection afforded to the Spanish NP Network. Three study areas (SAs) were very stable in the analysed period in all their zones: Aigüestortes, Ordesa y Monte Perdido and Caldera de Taburiente. In turn, Teide and Doñana were the SAs where LULC changes were more abundant. Unsustainable LULC changes concentrate in NPs' peripheral areas, chiefly in their SIZs, with wildfires being the most widespread pressure in the analysed period. Teide's SA outstands due to its environmentally unsustainable recent LULC changes, with urbanisation and wildfires affecting natural and semi-natural areas. Sustainable territorial planning and management practices should prioritise this SA. Highlights: Land use-land cover changes and wildfires were assessed in Spanish National Parks. Peripheral areas experienced more LULC changes and wildfires than national parks. Aiguestortes and Ordesa y Monte Perdido were the most sustainable study areas. Teide experienced the most environmentally unsustainable recent trends in all zones. Wildfires were common in the network whereas land artificialisation was residual.